2014
DOI: 10.1186/ar4614
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen affects osteogenesis of human mesenchymal stem cells via regulation of Indian hedgehog signaling molecules

Abstract: IntroductionWe previously showed that type X collagen, a marker of late stage chondrocyte hypertrophy (associated with endochondral ossification), is constitutively expressed by mesenchymal stem cells (MSCs) from osteoarthritis patients and this may be related to Naproxen (Npx), a nonsteroidal anti-inflammatory drug used for therapy. Hedgehog (HH) signaling plays an important role during the development of bone. We tested the hypothesis that Npx affected osteogenic differentiation of human MSCs through the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…(11,12) In addition, these results indicated that Npx can affect gene expression during osteogenic differentiation of MSCs through IHH signaling. (7) Elevated basal COL10A1 expression in OA MSCs also involved the activation of MAPK pathway and stimulation of the 5-lipoxygenase signaling pathway by Npx. (13) The present study is the first to demonstrate that Npx can regulate chondrogenic differentiation by affecting repair.…”
Section: After the Cells Were Cultured For 3 Days In Chondrogenic Difmentioning
confidence: 99%
See 4 more Smart Citations
“…(11,12) In addition, these results indicated that Npx can affect gene expression during osteogenic differentiation of MSCs through IHH signaling. (7) Elevated basal COL10A1 expression in OA MSCs also involved the activation of MAPK pathway and stimulation of the 5-lipoxygenase signaling pathway by Npx. (13) The present study is the first to demonstrate that Npx can regulate chondrogenic differentiation by affecting repair.…”
Section: After the Cells Were Cultured For 3 Days In Chondrogenic Difmentioning
confidence: 99%
“…(7) The effect of Npx on the expression of PTC1, IHH, GLI1, GLI2 and GLI3 when MSCs were cultured in chondrogenic differentiation medium was therefore assessed ( Figure 5). When the cells were cultured in this medium with Npx, the expression of PTC1 significantly decreased on day 6, compared with that in control cells ( Figure 5A).…”
Section: After the Cells Were Cultured For 3 Days In Chondrogenic Difmentioning
confidence: 99%
See 3 more Smart Citations